(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
this article is devoted to the usage of different learning styles. Children learn at different speeds due to a combination of biological, psychological, and environmental factors. This article explores the key reasons why some children learn quickly while others take longer, highlighting the role of brain development, learning styles, motivation, parental involvement, and social influences. It emphasizes the importance of understanding individual differences and creating supportive environments to help every child reach their full potential. By addressing these factors, parents and educators can enhance the learning process and foster better outcomes for children.